Socio-Economic Profile and Perception of Pepper Smallholders on the Use of Information Technology - Bahtera, Novyandra Ilham; Evahelda, Evahelda; Atmaja, Eddy Jajang Jaya; Irwanto, Riko (JIA (Jurnal Ilmiah Agribisnis) : Jurnal Agribisnis dan Ilmu Sosial Ekonomi Pertanian, 2021)
The economic growth in the agriculture sector contributes to the income of the Bangka Belitung Island Province. In the few decades, pepper production in Indonesia retains its position as one of the biggest producers in the world. However, pepper production in the province goes down. Consequently, the income of pepper farmers reduces. Understanding the farmers' demographic and their perception of the technology acceptance model will help policymakers provide the best empowerment program and agricultural support program to uplift their welfare. The study aims to understand the socio-economic profile and the perception of pepper farmers towards the technology acceptance model using information technology in pepper farming activity. The data collection process was conducted from August to November 2019. Structured questionnaires and face-to-face data collection methods were applied to earn the primary data from 100 pepper smallholders in Bangka Tengah and Bangka Selatan, Bangka Belitung Island Province. Descriptive analysis was used to identify the respondents' profiles and explain their skills and awareness to adopt information technology in their farming activity. The study revealed that most of the pepper farmers were in the average age of 45 years old, held elementary school level, received income of about 5.7 million, was experienced farmers with 20 years of pepper farming activity, and had about 2.1 – 5 ha of land area. The majority of the pepper smallholders offered low scores to the proportion of perceived usefulness and perceived ease of use. The results benefit the policymaker and farmer in providing a better farming activity and offering the best program to empower pepper farmers.